Military jargon in the Slovenian translation of Hostile waters - Zupan, Simon (ELOPE (Ljubljana), 2014)
The article examines Slovenian translations of military jargon in the non-fiction novel Hostile Waters. In the introductory part, jargon is presented as a linguistic category as well as its main features in the novel. Next, select examples from the original text are compared to their Slovenian equivalents. The focus is on collocations and lexically dense nominal phrases. The comparison finds that most translation shifts in the target text occur because of incorrect interpretation of technical jargon expressions in the original. As a result, the target text reader perceives certain situations differently than the source text reader.
Keywords: dokumentarni romani; prevajanje; prevodni premiki; slovenski prevodi; translation; vojaški žargon